Advanced finite elements in civil engineering practice - Holzer, Stefan M. (Computer Assisted Methods in Engineering and Science, 2023)
New developments in structural analysis methods such as automatic error estimation, adaptive discretization control, and mesh generation are slowly becoming available in engineering practice. On the other hand, graphical interactive user environments and easy-to-use general purpose programs are prolific. Each of these new developments helps to ease the everyday work of the engineer, but only by joining tchem together in a unified framework and user environment, an entirely new class and generation of structural analysis tools on the computer can be generated. The present study suggests guidelines and principles how such a new generation of software can be brought about, and reports experiences with a prototype application that is already in practical use.